Management and survival for patients with stage-I hepatocellular carcinoma: An observational study based on SEER database. Issue 41 (9th October 2020) - Wu, Zhaoping; Chen, Weili; Ouyang, Ting; Liu, Hechun; Cao, Lingling
Abstract : Abstract: It is controversial regarding the treatment allocation for patients with stage I hepatocellular carcinoma (SI-HCC). The aim of the present study was to compare the long-term survival in SI-HCC patients undergoing liver transplantation (LT), liver resection (LR), local tumor destruction (LTD), or none. SI-HCC patients diagnosed between 2004 and 2015 were extracted from the SEER 18 registry database. Multivariable Cox models and propensity score matching (PSM) method were used to explore the association between surgical methods and long-term prognosis. A total of 5165 patients with stage I (AJCC, 6th or 7th) HCC were included in the study. Only 36.9% of patients diagnosed with HCC in stage I received surgical therapy. The incidence of LT was decreased over time ( P < .001). In the multivariable-adjusted cohort (n = 5165), after adjusting potential confounding factors, a clear prognostic advantage of LT was observed in OS ( P < .0001) compared with patients after LR. Patients undergoing LTD had a worse OS in comparison with patients who underwent LR ( P < .0001). Patients who received no surgical treatment had the worst OS ( P < .0001) among 4 treatment groups. In stratified analyses, the salutary effects of LT vs LR on OS were consistent across all subgroups except for a similar result in the noncirrhotic subgroup ( P = .4414). The inferior survival effects of LTD vs LR on OS were consistent across all subgroups, and even in the subgroup with tumor size < 3 cm ( P = .0342). In the PSM cohort, patients in LT group showed a better OS ( P < .001) than patients in LR group ( P < .0001) and patients undergoing LTD had a worse OS compared with patients who underwent LR ( P = .00059). In conclusion, LT offered a survival advantage compared with LR among patients with Stage I HCC. LT is the best surgical treatment for stage I HCC in patients with advanced fibrosis, whereas LR provides comparable long-term outcomes to LT in patients without advanced fibrosis and should be considered as the first-line surgical option. LTD can be used as an alternative method when LR and LT are unavailable. Abstract : Supplemental Digital Content is available in the text